An analytical study of intestinal parasitosis in children - Bhattacharya, Rituparna; Barik, Kanai Lal; Bhattacharya, Promukh; Paul, Uttam Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Intestinal parasitosis (IP) is an important public health problem worldwide, most commonly seen in school age children and lead to nutritional deficiency, anemia and impaired cognition. Dearth of data regarding parasitic prevalence in the pediatric population triggered such a retrospective study planned by the Departments of Pediatrics and Microbiology, of two Medical Colleges whereby all the symptomatic children (>1 year and <12 years, divided into less than 5 year and 5-12 year groups) were examined for IP. Methods: Total 1000 parasite positive stool samples were collected for a period of two years and included for the study. Routine macroscopic and microscopic (saline and Lugol’s iodine wet mounts) examinations were carried out for the presence of ova, cysts and parasites. Results: Out of the 1000 positive samples, Enterobius vermicularis was predominant with 287 (28.7%) of all cases. The next in order were Giardia lamblia 243 (24.3%), Entamoeba histolytica 219 (21.9%), Ascaris lumbricoides 143 (14.3%), Ancylostoma duodenale 39 (3.9%), Taenia 27 (2.7%) and others 42 (4.2%). The distribution of parasites were heavier among the 5 to 12 year group (74.6%) than the below 5 year one (25.4%), with single parasitic isolate. Lack of hygienic practices like open field defecation, faecal contamination of water and improper hand washing aggravate infestation. Conclusions: Thus our study revealed that steps are to be taken by both the government and society to promote healthcare awareness in mothers, and mass scale deworming through school campaigns in order to lower the parasitic burden in children.